Lifestyle, Physical Activity, Eating and Hygiene Habits: A Comparative Analysis Before and During the COVID-19 Pandemic in Student Population - Marija Sekulic; Dalibor Stajic; Aleksandra Jurisic Skevin; Aleksandar Kocovic; Radica Zivkovic Zaric; Nela Djonovic; Dragan Vasiljevic; Branimir Radmanovic; Marko Spasic; Katarina Janicijevic; Ivana Simic Vukomanovic; Jovan Niciforovic; et al. (Frontiers Media S.A., 2022)
BackgroundChanging daily habits such as diet, hygiene and physical activity may be some of the consequences of the COVID-19 pandemic. The aim of the study was to analyze the effect of this pandemic on lifestyle, physical activity, eating and hygiene habits among students.MethodsThis cross-sectional study involved 171 students from the Faculty of Medical Sciences, University of Kragujevac, Serbia. Data were statistically analyzed using Wilcoxon Signed-Rank test, Marginal homogeneity test and Chi-square test. The differences were considered statistically significant when p ≤ 0.05.ResultsIn this study, it was observed that the most common physical activity before the pandemic was walking, while during the pandemic was home exercising. Compared to the period before the pandemic, there was no difference in the time spent engaging in daily physical activity (p = 0.334). However, there was a significant increase in sitting time during the pandemic (p = 0.005). Difference was noticed in the use of breakfast, the number of meals, and the type of fat in the diet before and during the pandemic (p = 0.000). During the pandemic, there was an increase in the use of fruits (p = 0.000), vegetables, and nuts (p = 0.001), while the use of fast food and alcohol have decreased. During the COVID-19 pandemic, a significant increase in the use of dietary supplements was observed (40.2%), (p = 0.008).ConclusionsGiven that the COVID-19 pandemic is ongoing, certain changes in lifestyle observed in this study should be confirmed in more extensive population studies.